Estética e missão: o belo como estratégia de evangelização para os Arautos do Evangelho - Santos, Murilo Alexandre dos (2014)
We have displayed the roots from which the Arautos do Evangelho originated and also their initial mission and deeds, their charisma and its presence within the spectrum of contemporary Catholicism and their processes of expansion. We continue by investigating the sense of aesthetics, beautiful and sublime, as well as the reception and practical experience of the Arautos when it comes to the concepts above stated. We want to display the mission and the evangelization inside the Catholic Church and the Arautos do Evangelho as well. We were guided by the hypothesis that the aesthetics, the beauty and the sublime constitute the core of the evangelization mission carried out by the Arautos and it, simultaneously, portrays functional sense aimed at a restorative evangelization to attract former churchgoers and to retrieve the conservative aspects of the Catholicism. The origin, the charisma and the presence of the Arautos inside the spectrum of the contemporary Catholicism were displayed; the general concepts of aesthetics, beauty and sublime and regarding the understanding of the Arautos and in their evangelizing action